La danza folklórica como herramienta para el desarrollo de habilidades de motricidad gruesa en niños de 4 a 10 años en el estudio de Danza Inti Huayra - Moreta Moreta, Leslye Estefania (2026)
This research analyzes the pedagogical and didactic potential of dance to strengthen children's motor development. Methodologically, the study employed a mixed-methods approach with a non-experimental, descriptive, and cross-sectional design. It sought to understand how folk dance practices influence the development of gross motor skills such as coordination, balance, strength, and locomotion in children aged 4 to 10 years who regularly participate in activities of the Inti Huayra study. Empirical data was collected through a survey of a teacher, direct observation of children during dance activities, and observation of a dance class. Taken together, these elements allowed for the recording of spontaneous behaviors and movement patterns during the dance sessions. Preliminary results suggested that folk dance, by integrating rhythmic, choreographic, and cultural elements, significantly promotes the development of gross motor skills in early childhood. Pedagogical strategies based on folk dances were proposed to optimize the development of gross motor skills in children. Furthermore, the value of this type of dance as an educational tool that promotes cultural identity, physical discipline, and emotional expression in non-traditional educational contexts is highlighted